NILAI SYUMULIYAH, KAFA’AH DAN TASAMUH DALAM TAFSIR SURAT AL-HUJURAT AYAT 13 - Nadri Taja; Giantomi Muhammad; Ramdan Fawzi; Labib Elmuna (LP2M Universitas PTIQ Jakarta, 2024)
This research examines religion and humanity from the perspective of the value of diversity referring to Surah al-Hujurat verse 13. A multicultural Indonesian society consisting of ethnic, cultural and religious aspects will have logical consequences for an attitude of understanding and respecting differences. So that diversity is seen as a necessity in all aspects of life without having to cause conflict. In the Qur'an, especially in Surah al-Hujurat verse 13, we find a portrait of a multicultural society as the embodiment of the symbol of Bhineka Tunggal Ika. In this research, the method used is a literature study with technical data analysis in the form of analytical descriptive. The findings of this research are values reflected in the opinions of the mufasir, namely the value of syumuliyyah, the value of kafa'ah and the value of tasamuh. These three values should be internalized and implemented in realizing the spirit of religion in the context of national and state life